(untitled) (Journal of the College of Basic Education, 2022)
Studying this subject is an attempt by me to shed light on one of the most important legal aspects of the property system in the Romans.The Roman laws are among the ancient laws codified in the world and the most mature of them in thought and law. And that the ancient Roman legislators when they legislated those laws were not just an idea written in lines and on tablets, but rather they were a sacred national duty imposed by their representatives in the land represented by kings for the purpose of achieving justice in Roman society.In this sense, these laws were distinguished by their strong intellectual and legal maturity.